Strategi Bimbingan Dosen Penasehat Akademik (DPA) Dalam Mengatasi Permasalahan Akademik Mahasiswa Di Iai Al-Qodiri Jember Tahun Pelajaran 2022/2023 - Fitriya, Anita (Childhood Education : Jurnal Pendidikan Anak Usia Dini, 2024)
Guidance and counseling activities are an integral part of education in Indonesia. As a professional service, guidance and counseling activities must be carried out as well as possible because it will support the success of the guidance given to students. Academic Advisor Lecturer (DPA), has the responsibility to provide guidance to students, in overcoming problems faced by students, especially those related to the academic field in their respective majors. In addition to carrying out their main duties, Academic Advisor lecturers (DPA) are tasked with communicating, guiding, motivating, and paying attention to students and helping to find and find solutions to problems faced by the students under their guidance. From the background above, the focus of this research is: 1). What is the form of academic advisory lecturer guidance services in overcoming student academic problems at IAI Al-Qodiri Jember. 2). What are the strategies for guiding academic advisors in overcoming student academic problems at IAI Al-Qodiri Jember. The research approach uses qualitative and the type of research design is based on case studies. In this study, researchers used porposive sampling and snow ball sampling techniques to determine informants. Data collection techniques in this study were participant observation, structured interviews, and documentation. Data analysis used the Miles & Huberman qualitative research model, namely: a. Data reduction (data reduction), b. Data presentation (data display) c. Drawing conclusions (verification). The results of the study show: 1) The form of the Academic Advisor Lecturer Guidance service in Overcoming Student Academic Problems at IAI Al-Qodiri Jember There are two forms of service provided to students, namely online and offline. Online academic advisor lecturers create groups on the whats app application to conducting guidance to students, in the group the lecturer provides information services and consulting services. a While offline academic advisor lecturers provide information services, consulting services and individual guidance services. 2) Academic Advisor Lecturer Guidance Strategies in Overcoming Student Academic Problems at IAI Al-Qodiri Jember, these strategies include strategies for providing motivation, religious guidance strategies and study guidance strategies. Keywords: Strategy, academic adviser lecturer guidance, student academic problems